Cyclic phosphonium ionic liquids - Lall-Ramnarine, Sharon I.; Mukhlall, Joshua A.; Wishart, James F.; Engel, Robert R.; Romeo, Alicia R.; Gohdo, Masao; Ramati, Sharon; Berman, Marc; Suarez, Sophia N. (Beilstein Journal of Organic Chemistry, 2014)
Ionic liquids (ILs) incorporating cyclic phosphonium cations are a novel category of materials. We report here on the synthesis and characterization of four new cyclic phosphonium bis(trifluoromethylsulfonyl)amide ILs with aliphatic and aromatic pendant groups. In addition to the syntheses of these novel materials, we report on a comparison of their properties with their ammonium congeners. These exemplars are slightly less conductive and have slightly smaller self-diffusion coefficients than their cyclic ammonium congeners.
Keywords: cyclic phosphonium; ionic liquid; organophosphorus; phosphinanium; phospholanium; phosphonium